Varieties of Language in North Acehnese and West Acehnese - Dina Sartika (Universitas Muhammadiyah Semarang, 2023)
Language and society are two things that cannot be separated, and each society has its own unique language. In addition, each community has its own unique language, which is known as the speech community since it is used by and understood by its members. The aims of the study to investigate varieties of language in speaker aspect in North Acehnese and West Acehnese and to investigate varieties of slang North Acehnese and West Acehnese. This study used descriptive qualitative design. The data of the research were collected through observations and interview to get the varieties in both regions. The findings obtained from this research show that four variations of speaker’s facet in Acehnese coming from North Acehnese and West Acehnese, namely idiolect, dialect, acrolectal, and slang. Turns out, both regions used different varieties although sometimes it may sound different strangely it still could be understood.